Advocacy Coalitions, Contestation, and Policy Stasis: The 20 Year Reform Process of the Colombian Health System. (June 2018) - Alvarez‐Rosete, Arturo; Hawkins, Benjamin
Abstract : This article analyzes the long process of health‐system reform in Colombia, using the advocacy coalition framework. Since its inception in 1993, the basic organizing principles and structures of the Colombian health system have remained highly contested, yet the system brought into effect by Law 100 has proven resilient to decisive reform. This article employs the advocacy coalition framework to explain this ongoing contestation and deadlock. It argues that the highly contested nature of the health system and policy stasis are the result of the power dynamics between three identifiable advocacy coalitions. The analysis of the legislative proposals submitted to the Congress of the Republic of Colombia between 1993 and 2014, reveals how the dominant coalition exploited mechanisms of the lawmaking process to impede Congress from passing successful new legislation. For the advocacy coalition framework, these mechanisms are Relatively Stable Parameters that constitute long‐term constraints and opportunities for subsystem actors. The article shows how Relatively Stable Parameters in the Colombian legislative system shaped the health‐system reform process.